Phonological Accent Preferences and Learning Patterns among EFL Learners - Yanti, Alya Dwi; Putri, Khairina Melani; Sitanggang, Juni Artha; Malau, Nova Anggriyani; Sinurat, Bloner (Universitas Pahlawan Tuanku Tambusai, 2025)
This research examines English language learning patterns and EFL students' pronunciation preferences for British and American accents. This research analyzes students' phonological preferences through formal and informal learning activities with the ultimate goal of improving English teaching methods. Data were collected through questionnaires and audio recordings. Closed-ended and The participants of this research consisted of 10 high school students from various schools in Pematangsiantar, North Sumatra, were selected through purposive sampling. open-ended questions were asked about students' English learning backgrounds, use of English-language media, and their opinions on accents. Audio recordings of students reading the narrative text